Induced premature ovarian insufficiency by using D galactose and its effects on reproductive profiles in small laboratory animals: a systematic review - Marzieh Rostami Dovom; Mahsa Noroozzadeh; Nariman Mosaffa; Azita Zadeh-Vakili; Abbas Piryaei; Fahimeh Ramezani Tehrani (BMC, 2019)
Abstract Background Development of a hyper-gonadotropic hypoestrogenism condition in women < 40 years, defined as premature ovarian insufficiency (POI), is the most common long-term complication in female survivors of galactosemia. In this systematic review, summarize the galactose (GAL) induced POI in rat and mice models. Methods For this systematic review, we conducted a search of case control studies published from 1990 until August 2018 in PubMed/Medline, and Web of science, using the descriptors in the title/abstract field. A 'pearl growing' strategy was employed whereby, after obtaining the full text articles, reference lists of all included studies (n = 14) were reviewed for additional publications that could be used. Results We selected and categorized 14 studies according to the time of exposure to GAL into two groups of prenatal (n = 4) and postnatal (n = 10). Findings of these studies showed that the different stages of follicular development are targeted differently by galactose exposure during the prenatal and postnatal periods: The small follicles (primordial and primary follicles) are targeted by galactose toxicity during prenatal exposure and the pre-antral and antral follicles are targeted by galactose toxicity during postnatal exposure. Conclusions This systematic review shows that galactose has an ovotoxicity effect that can be used to induce appropriate POI animal models only if sufficient doses, proper onset time, and duration of prenatal exposure are taken into account. An optimized model of POI induction should manifest all the required ovarian morphological, hormonal, and estrus cycle changes.